Designing feedback to mitigate teen distracted driving: A social norms approach. (July 2017) - Merrikhpour, Maryam; Donmez, Birsen
Highlights: A simulator study with 40 teens investigated a parental social norms intervention. Social norms, real-time, and post-drive feedback on distractions were compared. Both social norms and real-time feedback induced positive behaviors. Effects of social norms feedback were stronger and emerged sooner. Questionnaires show that teens may overestimate parental norms on distraction. Abstract: Objective: The purpose of this research is to investigate teens' perceived social norms and whether providing normative information can reduce distracted driving behaviors among them. Background: Parents are among the most important social referents for teens; they have significant influences on teens' driving behaviors, including distracted driving which significantly contributes to teens' crash risks. Social norms interventions have been successfully applied in various domains including driving; however, this approach is yet to be explored for mitigating driver distraction among teens. Method: Forty teens completed a driving simulator experiment while performing a self-paced visual-manual secondary task in four between-subject conditions: a) social norms feedback that provided a report at the end of each drive on teens' distracted driving behavior, comparing their distraction engagement to their parent's, b) post-drive feedback that provided just the report on teens' distracted driving behavior without information on their parents, c) real-time feedback in the form of auditory warnings based on eyes of road-time, and d) no feedback as control. Questionnaires were administered to collect data on these teens' and their parents' self-reported engagement in driver distractions and the associated social norms. Results: Social norms and real-time feedback conditions resulted in significantly smaller average off-road glance duration, rate of long (>2 s) off-road glances, and standard deviation of lane position compared to no feedback. Further, social norms feedback decreased brake response time and percentage of time not looking at the road compared to no feedback. No major effect was observed for post-drive feedback. Questionnaire results suggest that teens appeared to overestimate parental norms, but no effect of feedback was found on their perceptions. Conclusion: Feedback systems that leverage social norms can help mitigate driver distraction among teens. Overall, both social norms and real-time feedback induced positive driving behaviors, with social norms feedback outperforming real-time feedback.